Pemanfaatan Tepung Kulit Pisang Sebagai Sumber Energi Alternatif dalam Ransum Terhadap Performans Itik Raja - Abrani Sulaiman; Muhammad Riyadhi; Ahyadin Noor (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2014)
This study was aimed to determine the effect of banana peels as energy source in thediet on the performance of king duck, those were feed intake, body weight gain, final bodyweight, feed conversio, and Income Over Feed and Duck Cost (IOFDC). Research method inthis study was completely randomized design (CRD) with four treatments and five replications.Each replication consisted of three ducks, thus ducks used in this study was 60 head. Treatmentsin this experiment were KP0 (Without starchy banana skin (control) in the ration, KP1 = feedcontaining 12% flour banana peel in the ration, KP2 = feed containing 24% flour banana peelin the ration, and KP3 = feed containing 36% flour banana peel in the ration. The use ofbanana peels flour in treatment KP1 was effective as indicated by feed consumption, bodyweight gain, liveweight, and feed conversion. However, the highest weight gain and liveweightwere obtained from control treatment, that were 758.67 and 1106.67 g / head, respectively.